What can we learn from records of past eruptions to better prepare for the future - Pyle, D (Springer, Cham, 2017)
There is a long and rich record of historical observations of volcanic activity that has the potential to enhance current understanding of volcanic eruptions and their impacts, and to inform planning of responses to future events. However, apart from a small number of well documented examples, much of this broader material remains unread and little used. In this chapter, we explore examples of contemporary observations and accounts of volcanic eruptions at Santorini (Greece) and the Soufrière, St. Vincent, in the 18th, 19th and early 20th centuries. We show how these sorts of data could be used to inform and advance our understanding of, and approach to, volcanic crises; and to better understand the roles that communication—of hazards, of past events, or during an emerging crisis—may play in helping to prepare for the future.